A partially restrained energy dissipater: Parametric analysis and application in rocking wall. (May 2022) - Lu, Yujie; Liu, Ye; Lv, Qingfang
Abstract: To solve the limitations of the large-scale buckling-restrained brace and expand its application in rocking structures, a partially restrained energy dissipater (PRED) was developed recently. The partially restrained mechanism and the hysteretic behavior of PREDs have been verified by tests, whereas systematic studies of the PRED considering various design parameters have not yet been formed. In this study, parametric analyses of the PRED based on five series of numerical cases were conducted, which aimed at comprehensively studying the effect of the out-of-plane gap, length and number of the yielding segments, edge chamfering and thicknesses of the restraining tube on the seismic performance of the PRED and providing design recommendations. It is determined that the equivalent viscous damping ratio and compression-strength adjustment factor of the PRED decreased with the increasing out-of-plane gap. The overall hysteretic behavior and energy dissipation capacity were almost not affected by the number of yielding segments and their length. The thickness of the restraining tube should be equal to 4 mm or larger to avoid local plasticity. A detailed design procedure for PREDs was established based on the numerical analyses. Finally, PREDs were applied in a previously tested cross-laminated bamboo (CLB) rocking wall numerically to investigate the effectiveness of the PRED in rocking structures. The results showed that the energy dissipation and stiffness of the CLB rocking wall can be significantly improved by PREDs. This study lays a foundation for the application of the PRED in actual rocking structures and promotes the development of high-rise bamboo structures. Graphical abstract: Unlabelled Image Highlights: Parametric analyses considering 5 parameters of the PRED are conducted. A detailed design procedure of the PRED is proposed. The seismic performance of a rocking wall installed with PREDs is investigated.